The Effects of Religious Commitment on Psychological Stress among the Students of Tripoli University - Osama Omar M. Elazzabi (Universiti Sains Islam Malaysia, 2024)
This study aimed to investigate the effects of religious commitment on psychological stress among the students of Tripoli University, Libya. It also attempted to identify the casual relationship between religious commitment and the stress on one hand and some selected demographic variables such as gender, year of study, CGPA and faculty on the other hand. A number of 800 respondents were randomly selected from targeted population used stratified random technique. These numbers represented eight faculties of the university, namely faculty of Law, Science, Engineering, Agriculture, Arts, Human Sciences, Economics and Physical Education. The researcher adopted psychological stress scale of Dukhan and Hajar (2005) to examine students level of stress, while constructed Religious commitment scale due to unavailability of appropriate instrument precisely measure what he intended to measure. Many tests were used to test the reliability and validity of the used scales such as Cronbach’ alpha, Principal Component Analysis (PCA) and Confirmatory Factor Analysis (CFA) and the results suggested that both scales psychometrically sound, valid and reliable. Furthermore, the Structural Equation Modeling (SEM) was employed to tested the suggested model and test its invariance across gender and faculty while Multivariate Analysis of Variance (MANOVA) was employed to examine Stress and Religious Commitment across gender, year of study, CGPA and Faculty. The analysis suggested that there is a positive reciprocal statistical significant between religious commitment and psychological stress among the students. Interestingly, the analysis also indicated a positive relationship between Religious Commitment and academic achievement on one hand, while psychological stress negatively affect students’ academic performance on the other hand. Additionally, results also showed that there were statistical significant differences in the level of religious commitment and stress across gender, CGPA, year of study and faculty. It was found that male students were more stressful and more committed compared to their female counterparts, while high performance students were more stressful and committed than their low performance fellows. Finally, the analysis also suggested that final year students were more stressful and committed than their first, second and third years counterparts, while the result was overlapping between arts and science faculties.